Impacts of Off Take Rate through Small Ruminant Marketing on Food and Nutrition Security, Greenhouse Gas Emissions and Adaptive Capacity in Extensive Systems in Ethiopia: A Narrative Review - Dussie, Tsegaye; Chalchisa, Tamiru; Bekele, Yadeta; Mekuriaw, Shigdaf; Van Dijk, Suzanne; Makonnen, Brook (International Livestock Research Institute, 2025)
Ethiopia’s small ruminant sector is a cornerstone of rural livelihoods, contributing significantly to food security, income, and climate resilience. However, the marketing system remains inefficient, constrained by poor infrastructure, price volatility, and limited access to formal markets. This review examines the interplay between small ruminant off-take rates and three critical dimensions: food and nutrition security, greenhouse gas (GHG) emissions, and adaptive capacity in extensive production systems. The review process adopted the PRISMA model and entirely relied on secondary data. A total of 40 articles and study reports were used in the study. Findings reveal that Ethiopia’s four-tier marketing structure, comprising primary, secondary, terminal, and informal cross-border channels, is dominated by informal transactions (85%), with producers receiving only 35–45% of the final consumer price due to exploitative intermediaries. Low offtake rates (20–30%) reflect risk-averse strategies but limit meat supply and income potential, while high offtake risks deplete breeding stocks and undermine resilience. Small ruminants contribute ~30% of agricultural GHG emissions, yet optimized offtake and improved feeding practices could reduce emission intensities. Emerging innovations, such as mobile-based market information systems and cooperative marketing, demonstrate promise in enhancing equity and efficiency. Investing in market infrastructure, encouraging climate-smart behaviour, and putting policies in place that strike a balance between sustainability and productivity are some of the main recommendations of this study.